Coordination of power network operators as a game-theoretical problem - Martin Palovic (Jacobs University Bremen, Bremen Energy Research (BER), 2022)
We analyse incentive problems in coordination of network operators that purchase services for electricity networks from distributed resources. Such services are often associated with externalities that make the social optimum costly against the individual one. However, a costly reaction of other operators occurs when the social optimum is missed. Regular network situations result in game-theoretical problems like prisoner's dilemma or chicken that are played in a random order in an infinitely repeated game. The outcome of this complex gametheoretical setting, i.e. adopted strategies, is difficult to predict. Adjustments to network regulation aiming to internalize external effects are discussed as a remedy.
Keywords: 330